Effect of Administration of Different Concentrations of Bran in Fermetodege Feed on the Sheep Spermatozoa Quality - Nenotek, Roberto Charles; Ducha, Nur; Isnawati, Isnawati (LenteraBio : Berkala Ilmiah Biologi, 2024)
The objective of this study was to detemine the effect of rice bran on fermented feed towards the quality of sheep semen based on the viability and motility of spermatozoa. This study was experimental type that applied completely randomized design which is divided into three treatments, with five repetitions for each treatment. Each treatment represented the concentration of rice brain in sheep feed, namely 10%, 20%, and 30%, respectively. The test subject in the study were five Gibas sheeps which had been observed for 20 weeks. The results of this study indicated the rice bran with a concentration of 30% had the best effect on viability and motility of spermatozoa, namely 42±1.41 dan 47±0.83. Based on these results it can be concluded that rice bran influenced the quality of sheeps semen.